Measuring income risk - Simon M. Burgess; Karen Gardiner; Stephen P. Jenkins; Carol Propper (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
We provide a critique of the methods that have been used to derive measures of income risk and draw attention to the importance of demographic factors as a source of income risk. We also propose new measures of the contribution to total income risk of demographic and labour market factors. Empirical evidence supporting our arguments is provided using data from the British Household Survey.
Keywords: 330; Einkommen; Risiko; Haushaltseinkommen; Erwartungstheorie; Ökonometrisches Modell; Schätzung; Theorie; Großbritannien